ANALYSIS OF THE INFLUENCE OF WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT. CAHAYA ALAM SEJATI - Nainggolan, Renti; Silalahi, Flora; Surbakti, Eka Wulandari (Cattleya Darmaya Fortuna, 2025)
This study aims to analyze the influence of the work environment on employee performance at PT. Cahaya Alam Sejati, a packaging company based in Medan, Indonesia. A quantitative approach was employed using a survey method, with data collected from 108 permanent employees through a structured questionnaire distributed via Google Form. The work environment variable encompasses physical aspects (lighting, noise, room temperature), social aspects (relationships with colleagues and supervisors), and psychological aspects (stress and work pressure). Data were analyzed using simple linear regression with SPSS software. The results indicate a significant positive effect of the work environment on employee performance, with a significance value (Sig.) of 0.000 < 0.05 and a t-value of 6.395. The coefficient of determination (R²) is 0.278, indicating that 27.8% of the variation in employee performance can be explained by the work environment, while the remaining 72.2% is influenced by other factors such as motivation, leadership, and compensation. These findings underscore the importance of a supportive and conducive work environment in enhancing employee productivity and job satisfaction. It is recommended that management continue to improve both physical and psychosocial working conditions to foster better performance outcomes.